THE ROLE OF THE NATIONAL WARNING AND REPORTING SYSTEM IN DEFENSE SYSTEM TIMES OF CURRENT THREATS - Sławomir Kleszcz (Defence Science Review, 2017)
The article discusses selected issues related to the role of the national warning and reporting system in the defense system of the state. Explains the essence of its functioning and internal realities. It is an attempt to indicate further directions of its improvement and development.